Corrosion of CrN-Coated stainless steel in a NaCl solution (w = 3 %) - (:unkn) unknown (Institute of Metals Technology, 2015)
A CrN coating deposited by arc PVD was characterized by XRD and SEM. The in-situ measurement of the corrosion of the CrN-coated substrate was made by corrosion potential (Cor. Pot.), the polarization resistance (PR) method and electrochemical impedance spectroscopy (EIS) in a NaCl solution w = 3 % as a function of the immersion time (about 24 h). A semiconductor scale that formed on the CrN was identified by Mott-Shottky analysis as a p-type semiconductor with flat band potentials, 0.49 V (SCE). The CrN coating (0.5 μm thick) consisted of a mixture of cubic Cr and hexagonal Cr2N phases exhibiting equiaxed grains and a dense coating with a small quantity of pinholes, voids and porosities. The "transition in corrosion resistance" for the CrN coatings at an early stage was found based on Cor. Pot., PR and EIS data. The CrN did not exhibit any pitting for about 24 h, while the corrosion resistance (Rp and Rtotal) decreased rapidly with time after 5 h of incubation. The transition from high resistance (3 Mω cm2) to low resistance (0.24 Mω cm2) was explained as a result of the penetration of the electrolyte through the Cr2O3 oxide layer to the Cr2O3/CrN interface. The resistance of the CrN against pitting corrosion was explained based on the blocking character of the equiaxed, dense, CrN coating against the penetration of the electrolyte.
Keywords: Coating; CrN; EIS; Pitting corrosion; Polarization resistance; Stainless steel